Konsep self-esteem serta implikasinya pada siswa - Refnadi Refnadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
The process of achievement is an important part in the achievement itself. Achievement should be the result of honest hard work. In fact, to get the achievement, there are still many done with the road that is not good. One reason is the low self-esteem than students have. This text will describe the concept of self-esteem and the importance of students having a high self-esteem.